2023
DOI: 10.1037/xge0001423
|View full text |Cite
|
Sign up to set email alerts
|

Economic inequality reduces sense of control and increases the acceptability of self-interested unethical behavior.

Abstract: Societies worldwide are witnessing higher levels of economic inequality. While prior work has examined ethical judgments toward inequality itself (e.g., “is inequality unethical?”), less is known about how inequality shapes judgments of unethical behavior (e.g., “is unethical behavior more acceptable?”). In two correlational studies, we find that higher objective (Study 1; n = 127,953) and subjective (Study 2; n = 806) inequality is associated with greater acceptability of self-interested unethical behavior. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 116 publications
0
7
0
Order By: Relevance
“…Taken together, this past research leads us to predict that when people perceive more inequality, they will become more likely to expect others and themselves to act more unethically. In line with this, recent research showed that when perceived and actual levels of inequality were higher, people found unethical behavior of others to be more acceptable [ 25 ].…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…Taken together, this past research leads us to predict that when people perceive more inequality, they will become more likely to expect others and themselves to act more unethically. In line with this, recent research showed that when perceived and actual levels of inequality were higher, people found unethical behavior of others to be more acceptable [ 25 ].…”
Section: Introductionmentioning
confidence: 69%
“…Economic inequality has been increasing over recent decades, and this is problematic because inequality has been associated with several negative consequences [e.g., 1 , 16 ] including more unethical behaviors [e.g., 4 , 6 ], and the acceptance of unethical behaviors by others [ 25 ]. The present research suggests that perceiving high levels of inequality leads people to expect that they will act more unethically.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations